FALSAFAH PELA GANDONG DAN TOLERANSI BERAGAMA DALAM MASYARAKAT AMBON YANG MULTIKULTUR - A. Basir Solissa (UIN Sunan Kalijaga Yogyakarta, 2014)
This article is an effort to elaborate Ambonese Philosophy of Pela Gandong. The Society of Ambonese build up a wisdom called as Pela Gandong. It is a philosophy on how to bridge the differentiation between the peoples by its different in Religion and Culture. The Pela-Gandong cultural system is a bond of friendship and brotherhood expressed in familiar greetings such as Nyong Pee, Nona Pee, Gandongee, Bongsoee. It also covers activities of mutual cooperation in a better or worse situation,